(untitled) (Ustozlar uchun, 2026)
Tourism is the temporary movement of people to destinations outside their usual environment for leisure, business, or other purposes, involving a stay of at least one night but less than one year. It is a major industry providing services such as transportation, accommodation, and entertainment to travelers.